A Hybrid Stereoscopic Video Coding Scheme Based on MPEG-2 and HEVC for 3DTV Services - Taeyoung Na; Sangsoo Ahn; Sabirin, Houari; Munchurl Kim; Byungsun Kim; Hahm, Sangjin; Keunsik Lee (IEEE transactions on circuits and systems for video technology, 2013)
Recently, 3DTV has drawn much attention as a new broadcasting service. In spite of technical advances in 3DTV broadcasting services, there are two barriers that hinder the new services from being launched for terrestrial broadcasting: the lack of available bandwidth for transmission of additional-view video via terrestrial channel and backward compatibility with the legacy 2-D HDTV services. As an alternative, a hybrid stereoscopic video coding scheme is proposed for a stereoscopic 3DTV service, where one-view video is transmitted through the legacy broadcasting systems and the other one is delivered via broadband networks to which TV terminals are connected. In this paper, the proposed hybrid stereoscopic video coding scheme incorporates an MPEG-2 codec for backward compatibility with a legacy 2-D HDTV service and an HEVC codec with inter-view prediction coding as an extension to encode additional-view video sequences with high coding efficiency. The proposed inter-view prediction coding scheme in the extended HEVC incorporates an advanced motion and disparity vector prediction (AMDVP) method for enhanced motion- and disparity-compensated coding. The experimental results demonstrate that the proposed hybrid stereoscopic video coding scheme achieves an average coding efficiency of 38.22% (32.86%) in BD-rate or 1.394 dB (1.235 dB) in BD-PSNR for the out-band (in-band) scenario.